Health Behaviour among Nurses Working in Public Hospitals in Kakamega County, Kenya - Mchidi Kiguhe Nebert; B. M. Okello Agina; Yitambe Andre (Hindawi Limited, 2017)
Health behaviour refers to actions undertaken by a person who perceives self to be ill for the purpose of finding an appropriate remedy. Nurses as gate keepers of health are expected to seek formal treatment when they are taken ill because this is what they teach their patients. Nurses' working conditions all over the world are described as squalid with long working hours and workload. This scenario predisposes them to occupational health hazards and at the same time denies them time for self-care. Although nurses are knowledgeable about disease and its treatment and have access to health care, they engage in self-treatment in contrast to what they teach patients. Health behaviour among nurses in Kakamega County was investigated using a cross-sectional design. Data was collected using self-administered questionnaires and subjected to bivariate and logistic regression analyses. The study found that health behaviour of nurses in Kakamega County is below expectation, as 33% (n=61) engaged in voluntary screening services. Further, 34.8% (n=65) said that their health would improve if they engaged in health promotion activities. The study recommends empowering nurses to engage in positive health behaviour through education. The county should also provide affordable screening services to its nurses.